Enhancing intraoral radiographic technique: introducing “Nallan's Lines” - Chaitanya, Nallan CSK; Padmanabhan, Vivek; Islam, Md Sofiqul; Hashim, Nada Tawfig; Mohammed, Riham; Allam, Neeharika Satyajyothi; Omar, Jouma Jalal; Zakaria, Ahmed; Pranathi, Shaga; Apoorva, Mamindla (Frontiers in Oral Health, 2024)
BackgroundIntraoral radiography remains the most widely employed dental radiographic technique for producing geometrically accurate images with minimal distortion and magnification. Despite its common use in the dental office, incorrect projection geometry can be challenging leading to image distortions. To mitigate these inaccuracies specific radiographic landmarks on the face are utilized during periapical radiography. Nallan's lines, proposed in this study may address the perpetual issue.Material and methodsIn this cross over study, the participants were divided into 2 groups, Group A and Group B comprising nine in the each group. The bisecting angle technique was performed by the participants using a gyroscopic device fitted with a LASER with (Study subjects) and without (Controls) utilizing Nallan's lines on a selected group of teeth using a phantom model. Subsequent images were compared with those images obtained by an oral radiologist using the same model for geometric distortions of the images. This comparative analysis aimed to identify potential geometric distortions within the generated imagesResultsA paired t-test was employed to compare the mean length and breadth of teeth before and after radiographic training. Additionally, a McNemar Test was used to assess the impact of Nallan's lines on technical errors. Both analyses revealed statistically significant improvements post-training (p < 0.01). To determine if radiographic training affected the performance of volunteers and specialists, a Chi-Square Test was conducted to compare error rates. No statistically significant differences were observed between the two groups, both before and after training.ConclusionThe adoption of Nallan's lines may enhance the accuracy and quality of intraoral radiographic images. By adhering to this geometric framework dental practitioners can minimize geometric distortions and thereby repeated radiographic exposures of patients.